2021
DOI: 10.1002/aur.2636
|View full text |Cite
|
Sign up to set email alerts
|

Eye gaze as a biomarker in the recognition of autism spectrum disorder using virtual reality and machine learning: A proof of concept for diagnosis

Abstract: The core symptoms of autism spectrum disorder (ASD) mainly relate to social communication and interactions. ASD assessment involves expert observations in neutral settings, which introduces limitations and biases related to lack of objectivity and does not capture performance in real-world settings. To overcome these limitations, advances in technologies (e.g., virtual reality) and sensors (e.g., eye-tracking tools) have been used to create realistic simulated environments and track eye movements, enriching as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 53 publications
2
22
0
Order By: Relevance
“…Recent studies have confirmed that the use of avatars in virtual reality reduces anxiety in various populations [12][13][14]. While all demographics in studies reported being at ease in engaging with avatars in immersive social environments, introverts, and those with social anxiety disorders, PTSD, and ASD were better able to engage in social virtual reality more effectively than in person [15][16][17][18].…”
Section: Methodsmentioning
confidence: 90%
“…Recent studies have confirmed that the use of avatars in virtual reality reduces anxiety in various populations [12][13][14]. While all demographics in studies reported being at ease in engaging with avatars in immersive social environments, introverts, and those with social anxiety disorders, PTSD, and ASD were better able to engage in social virtual reality more effectively than in person [15][16][17][18].…”
Section: Methodsmentioning
confidence: 90%
“…Related research has demonstrated that eye gaze patterns and visual attention in an IVR simulated environment may be a useful biomarker for ASD diagnosis [ 16 ]. Outside of the IVR environment, gaze preferences between social scenes and non-social scenes [ 17 ], as well as pupillary responses during visual scanning activities have also been suggested as potentially useful in diagnostics for ASD [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…62 Despite this, ASD diagnosis is usually delayed until school age especially in mild to moderate cases of ASDs 63,64 ; since the early signs, such as repetitive movements or delayed talking might be misleading and considered normal by the parents or caregivers, or it may be misdiagnosed with attention deficit hyperactivity disorder (ADHD). [65][66][67][68] Although early diagnosis of ASD even in infancy is crucial for the proper management of this condition, there are limited to no accepted clinical biomarkers for its accurate diagnosis; instead, the current global approach being practiced for ASD diagnosis is majorly made based on interviews and standard questioners such as the DSM5 rather than laboratory tests. 10,65 Since the awareness for ASD has been raised in the world and especially in developing countries, finding a reliable diagnostic biomarker has been the focus of researchers in the field.…”
Section: Discussionmentioning
confidence: 99%